Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung - . Nurdiansyah (e-JKPP, 2016)
An Organization established because it has a goal to be achieved. Governmental organization founded with the purpose of providing services of civil rights and economic to every citizen optimally. Human resources is a central figure in the organization in achieving its expected goals. Management Order activities goes well, an organization must have the human resources knowledgeable and highly skilled and efforts to manage the organization as optimal as possible so that its performance is increased. The excellent performance is the optimal performance, the performance of the appropriate standards organization and support the achievement of organizational goals.Based on observations Employee performance Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung still low this can be seen from the popularity LAKIP (Government Performance Accountability Report) there are still some activity that has not reached 100%. In addition the level of employee discipline is still low. The phenomenon that occurred in the field of leadership style that is applied in the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung yet more effective work environment that is uncomfortable and office facilities were inadequate, it will affect the productivity of employees. Based on this background, the authors are interested to raise the issue in the context of preparing a thesis entitled influence leadership style and work environment the performance of employees working at the Badan Kesatuan Bangsa dan Politik Daerah Provinsi. The purpose of this study is to analyze the influence of leadership style and work environment the performance of employees working at the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung either partially or simultaneously. The technique of collecting data in this study is observation, interviews, questionnaires and documentation. The population in this study amounted to 80 employees of the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung. In this study the authors used data analysis descriptive and inferential In general the results of this research are as follows: 1) The leadership style positively on the performance of employees at the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung 2) Working Environment positive influence on employee performance at the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung 3) style of leadership and Environment work together positive effect on employee performance at the Badan Kesatuan Bangsa dan Politik Daerah Provinsi Lampung. Kata Kunci:  leadership style, workplace environment and performance of employees